Konten Islam di Media Televisi: Spiritualitas atau Pemasaran? - Hatta, Juparno (Journal of Religion and Film, 2023)
Islamic content has emerged on television media, appearing in the form of news, films, soap operas, talk shows, reality shows and so on. This is called the phenomenon of Islamic commodification, which is increasing in television media nowadays. This study attempts to see what is hidden behind the scenes in the process of presenting various popular cultural products with an Islamic image. Why is Islamic content on television media increasing? Was the action aimed at spiritual values or because of economic interests? Television products with religious content are the result of market intervention. The reason is, television is an industrial media with economic interests. As a media industry, television requires capital to develop its existence. In addition, media is developing into a capital-intensive aspect. Islamic content is produced to create audience loyalty, so that it can get good ratings. Meanwhile, audience is percentage data that is valuable to offer to advertisers. Islamic content is selected and produced to meet the tastes and appeal of the audience. Islam in broadcast media becomes a commercial object.